Bibliometrik Analisis: Teknologi Permainan Bidang Pendidikan Pada Sekolah Menengah Pertama - Rudi Kurniawan; Dadang Sudrajat (Ikatan Ahli Informatika Indonesia, 2024)
This study explores the use of game technology to enhance learning motivation and engagement among junior high school students in Indonesia. The background of the problem indicates low levels of learning motivation and student engagement in conventional learning processes. The root of this problem is linked to traditional teaching methods that are less engaging for students. This study aims to evaluate the effectiveness of game technology in addressing this issue. The research method employed a mixed methods approach involving a literature review, the development of educational game modules, and case studies in several junior high schools in Indonesia. The data used includes surveys on students' learning motivation, observations of student engagement, and interviews with teachers. The study also collected qualitative data from students' firsthand experiences in using game technology in learning. The results of the study demonstrate that the integration of game technology into the junior high school curriculum significantly increases students' learning motivation and engagement. Students who used educational games showed increased interest in the subject matter, were more active in class participation, and had a better understanding of the concepts taught. This study concludes that game technology is an effective tool for improving the quality of education in junior high schools and recommends a broader adoption of this technology in the Indonesian education system.